The Influence of Horray's Course Review Learning Model on Science Learning Outcomes at Islamic Elementary School - Sari, Intan Permata; Adriyani, Zuanita (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to determine the learning outcomes of students using the Course Review Horay learning model on the science subject for fourth-grade students at MI Nashrul Fajar Meteseh, Tembalang Subdistrict, Semarang. The study aims to investigate whether there are differences in learning outcomes between students using conventional teaching methods and those using the Course Review Horay model. This research is an experimental study with a quantitative approach. Data collection techniques include observations, interviews, tests, and documentation. The population of this study consists of all fourth-grade classes (A, B, C, D) at MI Nashrul Fajar Meteseh, with a total of 129 students. The sampling technique used in this study was purposive sampling, resulting in a sample of 63 students from fourth-grade classes A and B. The researchers employed field research methods, obtaining sources from official documents related to ecological spirituality and interviews with informants. Additionally, secondary sources such as books, journals, articles, and relevant literature reviews were utilized. The research design employed qualitative research, with data collected in the form of written or spoken language and observed behaviors. Due to the non-normal distribution of class data for normality and homogeneity tests, the non-parametric Wilcoxon formula was used to assess the impact of the Course Review Horay model on the study. The research findings indicate a significant difference in the learning outcomes of students using the Course Review Horay learning model compared to those using conventional teaching methods for science in the fourth grade at MI Nashrul Fajar. Based on the Wilcoxon test results, a significant value of 0.000 was obtained, which was smaller than 0.05. This implies that the alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected. Therefore, it can be concluded that the use of the Course Review Horay learning model has an influence on the science learning outcomes of fourth-grade students at MI Nashrul Fajar.